The factors that influence women to involve in business case study: Pasar Siti Khadijah, Kota Bharu Kelantan / Nor Ashikin Ibrahim - Ibrahim, Nor Ashikin (2013)
This study is to identify the factors that influence women to involve in business at Pasar Siti Khadijah. There are three factors that been studied, which are interest factor, family background and to gain profit. The objective of this study is to survey the business activities, factors they involve in business and to know the problems and perception that entrepreneurs faced. Data were gathered from the questionnaires which were distributed to 100 respondents from women entrepreneurs in Pasar Siti Khadijah. The entire questions in questionnaire are optional question and likert scale that required respondents to choose the right answer that relate with them. The data were analyzed using Statistical Packages for Social Science (SPSS) through the frequencies analysis, reliability test and chi square test. From finding, the researcher found out that all independent variables used in this study are significant and it related towards the dependent variable of the study. Most of the women entrepreneurs also involved in business because of the own interest and family business. Moreover, the researcher suggests some recommendations that suitable with the study in order to overcome the problems that faced by entrepreneurs.